Strengthening student communication skills through basic leadership training for OSIM members: Penguatan keterampilan komunikasi siswa melalui latihan dasar kepemimpinan OSIM - Muhammad Akhyar Aji Saputra; Fitriyatul Hanifiyah; Muhamad Yasin; Mohammad Faeruza Siva Alaba; Alif Dimas Wildany; Nida'ul Faiza; Samir al rasid; Muhammad Robiussani (KHD Production, 2026)
Effective communication is the cornerstone of productive and ethical interaction within educational ecosystems. This community service initiative aims to enhance the communication competence of madrasah students, focusing on speaking and active listening as fundamental pillars of leadership. The program was implemented at MTsN 2 Jember during the Student Council (OSIM) Basic Leadership Training for the 2025/2026 academic year. Utilizing a participatory training model, the program integrated interactive socialization, public speaking workshops, leadership simulations, and reflective peer discussions. A cohort of 30 OSIM members participated in the intervention. Results indicate a significant improvement in participants' self-confidence, critical listening abilities, and team-based communication strategies. Beyond technical skills, the training successfully fostered core leadership values, including responsibility, empathy, and peer motivation. This activity demonstrates that structured communication training is a strategic instrument for character building in secondary education and provides a scalable model for sustainable student leadership development.